1991
DOI: 10.2134/jpa1991.0074
|View full text |Cite
|
Sign up to set email alerts
|

Corn/Soybean Rotation Effect as Influenced by Tillage, Nitrogen, and Hybrid/Cultivar

Abstract: Information from the northern Corn Belt comparing tillage systems and corn (Zea mays L.)/soybean [Glycine max. (L.) Merr.] rotations over years is limited. Field studies were conducted near Arlington, WI for 3 yr (1987–1989) on a Plano silt loam soil (fine‐silty, mixed, mesic Typic Argiudoll). The objectives were to determine the influence of tillage, N fertilizer level, and hybrid/cultivar on growth and grain yield of corn and soybean grown in various rotation sequences. Yields of both corn and soybean declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 19 publications
8
87
1
Order By: Relevance
“…For corn, a yield benefi t for rotation has been widely reported, with results from 28 fi eld trial studies of crop rotation exhibiting, on average, a 7.8% increase in yield from the practice (Erickson, 2008) and a wide degree of variation across studies. Th e yield benefi t of rotation may derive from improved soil structure (Barber, 1972), decreased disease pressure (Meese et al, 1991), decreased allelopathy between corn residue and growing plants (Martin et al, 1990) and increased N availability for corn in rotated systems (Stanger and Lauer, 2008). Nitrogen availability, however, is thought to be the primary driver behind this benefi t (Gentry et al, 2013).…”
mentioning
confidence: 99%
“…For corn, a yield benefi t for rotation has been widely reported, with results from 28 fi eld trial studies of crop rotation exhibiting, on average, a 7.8% increase in yield from the practice (Erickson, 2008) and a wide degree of variation across studies. Th e yield benefi t of rotation may derive from improved soil structure (Barber, 1972), decreased disease pressure (Meese et al, 1991), decreased allelopathy between corn residue and growing plants (Martin et al, 1990) and increased N availability for corn in rotated systems (Stanger and Lauer, 2008). Nitrogen availability, however, is thought to be the primary driver behind this benefi t (Gentry et al, 2013).…”
mentioning
confidence: 99%
“…Throughout this analysis, there were obvious increases in both continuous corn cropping and continuous soybean cropping. Corn-soybean/soybean-corn rotation has long been considered beneficial to soil quality improvements and agricultural productivity [6,[8][9][10][11]. Therefore, a large transition into continuous corn or continuous soybean cropping would potentially lead to soil erosion and other environmental problems.…”
Section: Discussionmentioning
confidence: 99%
“…Corn and soybean may also be rotated with other forage crops like alfalfa or oats in different parts of the US [6]. Crop rotation can have a number of significant benefits, including improved soil quality [6,8], increased soil carbon sequestration [8], fewer crop diseases and pests [9][10][11] and consequently higher agricultural productivity [6,8]. However, to produce more corn and capitalize on higher prices, farmers tend to shift to continuous corn planting [12].…”
Section: Introductionmentioning
confidence: 99%
“…Crop rotation is an important management practice, the benefits of which result from many interacting factors. Previous studies have shown that, for various reasons, continuous soybean cultivation involves significant yield decrease in the long-term (Crookston et al, 1991;Kelley et al, 2003;Meese et al, 1991), has negative effects on soil water balance (SaladoNavarro and Sinclair, 2009), influences soil chemical properties, and increases disease pathogens. However, the benefits of crop rotation depend on which crops are included in the rotation, and in which sequence (Lund et al, 1993).…”
Section: Sample Characteristicmentioning
confidence: 99%